Single-cell deep phenotyping of IgG-secreting cells for high-resolution immune monitoring - Eyer K. (2017)
We would like to thank the Institut Pierre-Gilles de Gennes (IPGG) for use of clean room facilities and the laser engraver (CII08, Axyslaser), and Pfizer for the generous gift of TT-Alexa488, and CHO cell lines secreting TT4, TT7, and TT10. TT11 and TT27 antibodies are Pfizer proprietary antibodies isolated from their collaboration with HiFiBiO. We thank Pfizer (M. Holsti, G. Cheung, and W. Somers) as well as HiFiBiO Team (A. Gérard, A. Woolfe, M. Reichen, A. Poitou, S. Essonno, R. Kumar, S. Ellouze, K. Grosselin, B. Shen, and C. Brenan) for identification, rapid cloning, and validation of TT11 and TT27 antibodies. This work received support from the French Investissements d'Avenir program under the grant agreements ANR-10-NANO-02, ANR-10-IDEX-0001-02 PSL, ANR-10-LABX-31 and ANR-10- EQPX-34, by the French Agence Nationale de la Recherche (ANR-14-CE16-0011 project DROPmAbs), from Région Ile-de-France (DIM NanoK) and by the Institut Carnot Pasteur Maladies Infectieuses. K.E. acknowledges financial support from the 'Fondation Pierre-Gilles de Gennes', and the 'Swiss National Science Foundation' and the 'Society in Science—The Branco Weiss Fellowship'. C.C. acknowledges financial support from CONCYTEC, Peru. We would like to further acknowledge R. Henson for making the dscatter function for Matlab publicly available, M. Spitzer, J. Wildenhain, J. Rappsilber and M. Tyers for BoxPlotR that has been used to create the box plots, and B. Iannascoli (Unit of Antibodies in Therapy and Pathology, Institut Pasteur) for help with antibody production and cell lines.